Una nota sobre los estimadores de máxima verosimilitud en la distribución hipergeométrica (2009)
The method of maximum likelihood estimation is one of the most important statistical techniques, and it is widely used by statistical scientists. However for the hypergeometric distribution Hg(n,R,N), the maximum likelihood estimators of N and R are not clear in most of the statistical texts. In this paper, rigorous procedures in order to ﬁnd the maximum likelihood estimator of N and R in a hypergeometric distribution are presented.